BUDAYA AKADEMIK SEBAGAI SALAH SATU PENJAMIN MUTU PENDIDIKAN - I NYOMAN YOGA SEGARA (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
This article is the result of a review of academic culture which according to some research is still not good, even experienced by 10 major universities in Indonesia. Although the regulations governing academic culture already exist but it is difficult to be realized let alone in a hurry. There are many factors that affect academic culture not yet ideal. In general, what has happened in Indonesia has influenced academic culture on campus, such as low reading level and poor book availability. This is an external factor that determines internally the civitas academica. Culture of reading, writing and discussion is still not developed when this activity can be a habitus that if continuously disseminated will become a habit and culture. To read academic culture, this article is inspired by Abraham Maslow's opinion of needs and motivations while the concept of habitus, arena and capital is inspired by Pierre Bourdieu.